Avaliação da taxa de corrosão do aço AISI 1020 em petróleo bruto e padrões de ácidos naftênicos - Dias, Heloisa Pinto (2019)
It is common to use the total acid number (TAN) as a measure of the acidity of a Petroleum. However, naphthenic acids (NAs) vary in their structures and concentrations from one petroleum to another, even when the TAN value remains constant. Daily practice at the refineries has shown that oils with a NAT less than 0.5 mg of KOH·g-1 most often presents an unexpected corrosive behavior. Although naphthenic corrosion has been studied for years, its process is still not completely understood. Thus, the present study investigated the influence of solutions of molecules of linear, cyclic and aromatic NAs, (evaluating the effect of their concentrations, molar mass (Mw), and structural and electronic properties) in the corrosion rate under AISI 1020 steel, through tests at 320 ºC in 24H.The type and extent of corrosion were monitored by characterizing the surface of the specimens by light microscopy (LM), atomic force microscopy (AFM), and scanning electron microscopy (SEM). The results showed that, even when the TAN was below the limit of detection, the value of the observed corrosion rate (CR) was significant, being considered high (TC < 0.19 mm·year-1) by the oil industry. At concentrations ≥ 5000 ppm of benzoic acids (BENA) and stearic (STA), the corrosion rate varied proportionally to the TAN. In addition, there was an inversely proportional correlation between the molar mass (Mw) and the number of aromatic rings of the NAs with their corrosive capacity. It was observed that the NAs standards containing a lower molar volume presented a higher corrosion rate. The images presented by SEM showed changes in the surface of all coupons exposed to NAs solutions, indicating that a protective layer was formed under the surface of the carbon steel coupon. The images by AFM revealed a topographic and phase profile deeply altered by the formation of valleys and peaks and variations in the mechanical properties of the AISI 1020 steel surface. The results obtained in this study are promising and confirm the influence of the electronic structural properties of organic acid molecules under naphthenic corrosion.